(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
A research which antibacterial activity test from Prinjak plant (Aleurites moluccana (L.) Willd to several pathogens bacterial, which aims to determine the antibacterial activity of bark prinjak (A. moluccana L.) against bacteria Salmonella thyposa and Vibrio cholerae. Extracts used is crude methanol extract. Examination of antibacterial with Minimum Kill Concentration (KBM) method, and followed by agar diffusion method with using paper disks. ANOVA analisis test it is obtained very significant results, followed by BNJ advanced test, BNJ test obtained the best concentration is 1.75 % results of the bacteria Salmonella and Vibrio cholerae thiposa.